ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN FLORES TIMUR PERIODE 2015-2019 - Lebuan, Yakobus Jeksiano Sinu (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2022)
This study analyzes how the financial performance of the east flores district government in managing its regional revenue and expenditure budget, the analysis uses data from the 2015-2019 period. This study uses interviews and documents as data collection techniques. This study uses an analysis of the ratio of effectiveness, efficiency and growth to determine the performance of local governments in the management of APBD whether it includes effectiveness and efficiency standards and measures how much local government is capable of maintaining and reminding of its successes that have been achieved from period to period. The results of the analysis show that the average income effectiveness from 2015-2019 is 97.46, the average spending effectiveness level from 2015-2019 is 92.47%, the average revenue financing effectiveness rate from 2015-2019 is 99 .80%, the average level of effectiveness of expenditure financing from 2015 to 2019 is 96%, the average level of budget efficiency from 2015 to 2019 is 100.60%